Effect of Sputtering Power on the Structural and Optical Properties of Inn Nanodots on Al2O3 by Magnetron Sputtering - Zhang,Ziming (2019)
In this work, we reported the effects of sputtering power on the structure, optical and electrical properties of InN nanodots prepared on Al2O3 substrate by magnetron sputtering.The results showed that the as-grown InN films exhibited uniform nanodot morphology and the size of the InN nano grains increased with the sputtering power was increased. The InN nanodot exhibited highly c-axis prefered orientation with mainly InN (002) diffraction. The optical band gap of InN samples showed an decreasing trend with the increase in sputteirng power. Moreover, the electrical properties of the InN samples were discussed in detail by hall effect and the carrier concentration and mobility could be adjusted from 3.233×1019 to 1.655×1020 cm-3 and 1.151 to 10.101 cm2/v•s, respectively. These results will lay a good fundation for the applicaion of InN material in the field of gas sensers and light emitting diodes.